EGR-2 Is Not Required for In Vivo CD4 T Cell Mediated Immune Responses - Ramón, Hilda E. (Public Library of Science, 2010)
BACKGROUND: The zinc finger transcription factor EGR-2 has been shown to play an important role in the induction of T cell anergy and the regulation of peripheral T cell tolerance. In vitro, a prior study has show that T cells deficient in EGR-2 are hyperproliferative to IL-2 and produce elevated levels of the effector cytokine IFN-γ. EGR-2 deficient mice have increased levels of CD44(high) T cells in peripheral lymphoid organs, and with age, develop autoimmune-like features. PRINCIPAL FINDINGS: Here we show that despite increased numbers of cells bearing an activated CD44(high)CD62L(low) phenotype, T cells from young healthy EGR-2 deficient mice have normal proliferative and cytokine responses, and the mice themselves mount normal immune responses against minor histocompatibility antigens, and the pathogens Toxoplasma gondii and lymphocytic choriomeningitis virus. CONCLUSIONS: Our results indicate that EGR-2 is not required to mount normal acute in vivo immune responses against foreign antigens, and suggest instead that it may serve to regulate the response to chronic antigenic exposure, such as that which occurs to autoantigens.